Assessing Recent Soil Erosion Rates through the Use of Beryllium-7 (Be-7) - Mabit, Lionel; Blake, William (Springer International Publishing : Imprint: Springer, 2019)
This open access book is the first comprehensive guideline for the beryllium-7 (Be-7) technique that can be applied to evaluate short-term patterns and budgets of soil redistribution in agricultural landscapes. While covering the fundamental and basic concepts of the approach, this book distinguishes itself from other publications by offering step-by-step instructions on how to use this isotopic technique effectively. It covers experimental design considerations and clear instruction is given on data processing. As accurate laboratory measurement is crucial to ensure successful use of Be-7 to investigate soil erosion, a full chapter is devoted to its specific determination by gamma spectrometry. This open access contribution further describes new developments in the Be-7 technique and includes a concluding chapter highlighting its potential benefits to support the implementation of area-wide soil conservation policy.